Androgen receptor gene mutation, rearrangement, polymorphism - Eisermann, Kurtis; Wang, Dan; Jing, Yifeng; Pascal, Laura E.; Wang, Zhou (Translational Andrology and Urology, 2013)
Genetic aberrations of the androgen receptor (AR) caused by mutations, rearrangements, and polymorphisms result in a mutant receptor that has varied functions compared to wild type AR. To date, over 1,000 mutations have been reported in the AR with most of these being associated with androgen insensitivity syndrome (AIS). While mutations of AR associated with prostate cancer occur less often in early stage localized disease, mutations in castration-resistant prostate cancer (CRPC) patients treated with anti-androgens occur more frequently with 10-30% of these patients having some form of mutation in the AR. Resistance to anti-androgen therapy usually results from gain-of-function mutations in the LBD such as is seen with bicalutamide and more recently with enzalutamide (MDV3100). Thus, it is crucial to investigate these new AR mutations arising from drug resistance to anti-androgens and other small molecule pharmacological agents.